2015
DOI: 10.1242/dev.122226
|View full text |Cite
|
Sign up to set email alerts
|

Pvr receptor tyrosine kinase promotes tissue closure by coordinating corpse removal and epidermal zippering

Abstract: A leading cause of human birth defects is the incomplete fusion of tissues, often manifested in the palate, heart, or neural tube. To investigate the molecular control of tissue fusion, embryonic dorsal closure and pupal thorax closure in Drosophila are useful experimental models. We find that Pvr mutants have defects in dorsal midline closure with incomplete amnioserosa internalization and epidermal zippering, as well as cardia bifida. These defects are relatively mild in comparison to those seen with other s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 88 publications
2
15
0
Order By: Relevance
“…My data show that Pvr loss-of-function impairs cortex glia morphogenesis and survival. This is consistent with previous studies showing that Pvr signaling is required for trophic support and morphogenesis in other cell types (Brückner et al, 2004;Garlena et al, 2015;Parsons and Foley, 2013). I found that loss of Pvf-Pvr function decreased PI3K signaling in cortex glia, that loss of PI3K pathway components partially phenocopies Pvf-Pvr loss of function, and that restoration of PI3K signaling in glia partially rescued the effects of Pvr knockdown.…”
Section: Pvf-pvr Signaling and Cortex Glia Development And Functionsupporting
confidence: 92%
See 1 more Smart Citation
“…My data show that Pvr loss-of-function impairs cortex glia morphogenesis and survival. This is consistent with previous studies showing that Pvr signaling is required for trophic support and morphogenesis in other cell types (Brückner et al, 2004;Garlena et al, 2015;Parsons and Foley, 2013). I found that loss of Pvf-Pvr function decreased PI3K signaling in cortex glia, that loss of PI3K pathway components partially phenocopies Pvf-Pvr loss of function, and that restoration of PI3K signaling in glia partially rescued the effects of Pvr knockdown.…”
Section: Pvf-pvr Signaling and Cortex Glia Development And Functionsupporting
confidence: 92%
“…In Drosophila, Pvf-Pvr signaling activates PI3K, Ras-Map kinase, Rho-Rac and Cadherin pathways (Brückner et al, 2004;Cho et al, 2002;Duchek et al, 2001;Garlena et al, 2015;McDonald et al, 2003). Genetic and cell biological approaches were used to determine which of these pathways are required for cortex glia development downstream of Pvf-Pvr.…”
Section: Loss Of Glial Pvr Causes Loss Of Pi3k and De-cadherin Signalingmentioning
confidence: 99%
“…In the absence of OA Hmu, Cpr, and Gp93 localize in a reticular pattern. Pvr is enriched at the plasma membrane, as reported previously (72,73), and on intracellular membranes. The localization of Gp93 and Pvr does not change with OA addition, whereas Cpr and Hmu are now found in the vicinity of LDs.…”
Section: Fig 4 Identification and Confirmation Of Cg9186 Interactiosupporting
confidence: 84%
“…Given that previous works have regarded Drosophila thorax closure as a model of general epithelial wound closure because of the distinctive commonalities (Garlena et al, 2015;Martín-Blanco and Knust, 2001;Zeitlinger and Bohmann, 1999), we examined wound closure of pupal nota using a multi-photon laser scanning confocal microscope. Notably, cells with activated caspase 3 have been also detected around wounded sites.…”
Section: Cells With Sub-lethal Activation Of Caspase 3 Close Woundmentioning
confidence: 99%